2001
DOI: 10.1002/1521-3773(20010716)40:14<2712::aid-anie2712>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

New Paradigms for Organic Catalysts: The First Organocatalytic Living Polymerization

Abstract: A metal‐free approach to the living ring‐opening polymerization (ROP, shown schematically) of lactide has been developed using strongly basic amines such as 4‐(dimethylamino)pyridine as transesterification catalysts. These organic catalysts must be used in combination with a nucleophile such as an alcohol, which is the actual initiating species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
320
1
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 442 publications
(335 citation statements)
references
References 41 publications
3
320
1
3
Order By: Relevance
“…If a guest ion was present that selectively bound to one of the rings then the system could be moved to favor the presence of that host-guest complex ion. To test for this hypothesis, we introduced an isolated group of A n molecules in benzene solution to a suspension of NaBPh 4 . Upon heating to 60°C the A 6 rings were selectively removed from the solution as is evident from the mass spectra shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…If a guest ion was present that selectively bound to one of the rings then the system could be moved to favor the presence of that host-guest complex ion. To test for this hypothesis, we introduced an isolated group of A n molecules in benzene solution to a suspension of NaBPh 4 . Upon heating to 60°C the A 6 rings were selectively removed from the solution as is evident from the mass spectra shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have found that when the polymer support (1 eq based on N atom content) is allowed to react with L-LA (24 eq) in the presence of a suspension of NaBPh 4 (10 eq) in benzene at 80°C for 20 h, the A 6 rings are removed from solution with the formation of NaBPh 4 (MeCHC(O)O) 6 . The latter is soluble in acetonitrile, and based on the integration of the proton signals arising from BPh 4 Ϫ and A 6 in the 1 H NMR spectrum recorded in CD 3 CN the conversion of LA to A 6 is Ͼ80% based on NaBPh 4 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7] Since the biomedical application of the polymers demands extremely high purity and the absence of any toxic compounds, the development and use of biocompatible low-toxic or non-toxic catalysts/initiators, one of which is the metal-free organo-catalyst, may have significant benefits. [8][9][10] The most studied organo-catalytic compounds for the ROP of cyclic esters are some well-known transesterification agents such as 4-(dimethylamino) pyridine, 11 nucleophilic tertiary phosphines, 12 N-heterocyclic carbenes, 13 bifunctional aminothioureas, 14 and 1,5,7-triazabicyclo-[4.4.0]dec-5-ene. 15 Among these organocatalyst, the nucleophilic tertiary phosphines are quite interesting for their catalytic mechanism.…”
mentioning
confidence: 99%